Proton-transfer-steered mechanism of photolesion repair by (6-4)-photolyases - Faraji, Shirin; Dreuw, Andreas (The journal of physical chemistry letters, 2012)
DNA (6-4)-photolyases are enzymes initiating cleavage of mutagenic pyrimidine (6-4) pyrimidone photolesions by a photoinitiated electron transfer from flavin adenine dinucleotide to the lesion. Using state-of-the-art quantum chemical calculations, we present the first energetically feasible molecular repair mechanism. The initial step is electron transfer coupled to proton transfer from the protonated His345 to the N3′ nitrogen of the pyrimidone thymine of the lesion, which proceeds simultaneously with intramolecular OH transfer in a concerted reaction without formation of an oxetane or isolated water molecule intermediate. In contrast to previously suggested mechanisms, this newly identified pathway requires neither a two-photon process nor electronic excitation of the photolesion. Indeed, the recognition that the initial electron transfer is coupled to the proton transfer was critically important for clarification of the mechanism.
Gesehen am 18.12.2017